2013
DOI: 10.1016/j.jotr.2013.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Approaches, Pitfalls and Outcomes of Posterior Fracture Dislocations of the Shoulder—A Critical Review

Abstract: Posterior fracture dislocation of the shoulder is rare injury. Treatment is challenging especially for a complex type fracture dislocation with delayed presentation or a reverse Hill-Sachs lesion. We reviewed the surgical approaches, the reduction and fixation techniques, management of reverse Hill-Sachs lesion, pitfalls, and outcomes. We also shared our experience in treating a short case series of posterior fracture dislocation of the shoulder. There were no major complications such as wound infection, nerve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Although the true incidence of a spontaneously reduced tibiofemoral dislocation may be difficult to determine, none of our 78 patients in the non-dislocated group described a manual or spontaneous reduction occurring in the field. Initial evaluation should include a thorough patient history, physical examination, and imaging, with particular attention to vascular status, which has the greatest emergency treatment implications 31 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the true incidence of a spontaneously reduced tibiofemoral dislocation may be difficult to determine, none of our 78 patients in the non-dislocated group described a manual or spontaneous reduction occurring in the field. Initial evaluation should include a thorough patient history, physical examination, and imaging, with particular attention to vascular status, which has the greatest emergency treatment implications 31 .…”
Section: Discussionmentioning
confidence: 99%
“…All periarticular fractures of the tibiofemoral or patellofemoral joint that contribute to tibiofemoral instability were also included and were subclassified with use of the Moore classification 30,31 . Examples of these types of fracture-dislocations are shown in Figures 3 and 4.…”
Section: Methodsmentioning
confidence: 99%
“…Ho et al reported three approaches in the surgical treatment of this complex lesion, including the deltopectoral approach (two cases), the utility approach (four cases) and the deltopectoral approach combined with the limit posterior deltoid‐splitting approach (three cases). Similarly, Trikha et al reported the deltopectoral approach combined with the limited posterior deltoid‐splitting approach in six cases.…”
Section: Discussionmentioning
confidence: 99%